Healthy Principal Leadership Concepts - Vena Annisa Harahap (MUDABBIR Journal Reserch and Education Studies, 2023)
One of the goals of a healthy principal's leadership is to produce graduates who have achievements on a national and international scale. Therefore, healthy school principal leadership is influenced by the education system that supports it. In writing this article, we will discuss the characteristics of a healthy school principal's leadership and its role in the school, the method used is literature study. The findings from this research are to ascertain the characteristics and role of a healthy school principal's leadership, especially for school empowerment. The characteristics of healthy leadership behaviors that can encourage an effective school sustainability process include having visionary thinking, strong self-confidence and trusting others, strong will, courage and consistency. The role of leadership is very necessary in supporting the process of improving the quality of education, the behavioral characteristics shown by leaders will be able to influence and move individuals or groups in the organization they lead.